Enhancing soybean (Glycine max (L.) Merr.) yield on Inceptisol through the application of organic fertilizers to promote sustainable agriculture - Syaranamual, Siska; Baan, Samen; Martanto, Eko Agus; Metubun, Milda (Technium Sustainability, 2022)
Organic fertilizers have been considered as environmentally friendly fertilizers in promoting sustainable agriculture, being supported by the abundant natural resources. The study was conducted to determine the effect of type and level of dosage of organic fertilizers on soybean yield. The 4-month study was carried out in West Papua Province, Indonesia, compiled using factorial randomized block design (RBD). The factors were the types of organic fertilizer and two doses of the organic fertilizer. Parameters assessed include number of grains per pod, weight of 100 grains and weight of grains per plot. Pointed out the results of the analysis of variance, the various types of organic fertilizers used (F1, F2, F3 and F4) were significantly different in almost all components of growth and production. However, the type of goat manure (F4) gave the highest yield, while the type of fertilizer that gave the lowest yield was compost (F2). Fertilizer doses were significantly different in almost all yield parameters, namely D1 (5 tons/ha) compared to D0 (without fertilizer). The interaction with the highest yield was goat manure (F4D1), while the interaction that gave the lowest yield was without the use of compost fertilizer (F2D0). Given that high soybean yield can be achieved by balanced fertilization. One way to increase soil fertility in terms of providing nutrients for plants and harmless toward land and plant is by providing organic fertilizers.